Avaliação do rejeito mineral de scheelita e vermiculita na catálise do óleo da amêndoa de macaúba e do óleo de fritura para síntese de biodiesel - Moura, Taffarel Eloi de (2022)
Since it is produced from biomass and driven for energy self-sufficiency, a reduction in costs with the use of biomass oil and minimization of environmental problems. The biodiesel production process generally occurs through esterification and/or transesterification reactions, where an oil or fat reacts with an alcohol, in the presence of a catalyst, forming fatty esters (biodiesel) and glycerol (or water, in esterification case) as a co-product. The study focused on the use of heterogeneous catalysts to enhance the production of biodiesel has increased, mainly due to its numerous advantages over the use of homogeneous catalysts, such as its easy removal from the reaction medium and the reduction in the generation of chemical effluents. Among the solid catalysts, those originating from mining processes can exert significant advantages, because during the extraction of these minerals, tons of solid waste are generated that are deposited in the open air, occupying large areas and causing environmental and health impacts, which can be verified in the mining of vermiculite and scheelite, in which two types of tailings are produced, the first not yet sufficiently explored in the production of biodiesel, and the second unprecedented in this area. The physical-chemical behavior of minerals and their tailings have a promising catalytic activity, however, they need processes to enhance their catalytic properties. Given this scenario, and taking into account that vermiculite and scheelite are widely exploited in the Brazilian Northeast, in the states of Rio Grande do Norte and Paraíba, this study aimed to analyze the waste generated from this extractive activity, in its natural form (RVR, RVP and RSC) and chemically treated (RVRA, RVPA and RSCA), as catalysts in the esterification/transesterification reaction of macaúba kernel oil (OAM) and residual frying oil (OFR). The residual catalysts were characterized using XRD, FTIR, BET/BJH, Experimental Density, Zeta Potential, Granulometric Distribution, EDX, SEM and TGA/DrTGA techniques. The bench catalytic tests were carried out in two stages, the first being carried out under moderate conditions, in which a temperature of 180 ºC, an oil/alcohol molar ratio of 1:15, 2% of catalyst and a reaction time of 1 h were used. In this step, the best results were for the tests that used the catalysts RSCA and RVPA, which presented 28.75% and 73.72% of conversion into esters for the OAM and OFR oils, respectively. The catalysts RSCA and RVPA were selected for a second reaction step, under conditions considered more severe, in order to potentiate the catalysis and promote greater conversions, using a temperature of 200 °C, molar ratio 1:27, reaction time of 3 h and maintaining fixed only the amount of catalyst (2%). Thus, in the second batch of tests, conversions of up to 42.48% for RSCA and up to 58.11% for RVPA were obtained. Therefore, it can be said that the catalytic results were not relevant, possibly because the catalysts do not have sufficient amounts of accessible chemical sites, requiring further investigation in relation to their chemical treatment and reaction conditions.